Topological data analysis in medical imaging: current state of the art - Yashbir Singh; Colleen M. Farrelly; Quincy A. Hathaway; Tim Leiner; Jaidip Jagtap; Gunnar E. Carlsson; Bradley J. Erickson (Insights into Imaging, 2023)
Key points 1. Topological data analysis (TDA) provides information on the shape of data. 2. In radiology, the shape of 2D and 3D images contains additional information. 3. TDA can be combined with other applications, such as textural analysis. 4. Persistent homology can provide a visual representation of extracted TDA data.